Evaluating the Impact of Starter Fertilizer on Winter Canola Grown in Oklahoma - M. Joy M. Abit; Katlynn Weathers; D. Brian Arnall (International Journal of Agronomy)
Increased canola production costs and acres have driven Oklahoma (OK) farmers to ask more questions about their nutrient management recommendations in their production system. A study was conducted in 2011–2013 at Lahoma and Perkins, OK, to evaluate the effect of applying diammonium phosphate (DAP, 18-20-0:N-P-K) directly with seed on crop stand, grain yield, and grain quality of canola. In addition, the impact of proportion nitrogen (N) applied as a preplant and topdress was also evaluated. Diammonium phosphate was banded with the seed at planting at 0, 17, 34, 51, 67, and 84 kg DAP ha−1. Remaining N was applied as urea (46-0-0) either as split (40% preplant and 60% topdress) application or as topdress only. Stand count reduction of up to 71% was observed with seed-placed DAP. However, loss of stand did not impair grain yield due to canola’s ability to compensate for open areas via branching. Application of DAP of up to 84 kg ha−1 with seed may be possible; however, soil and climatic conditions should be considered when deciding how much DAP will be placed with seed. Moreover, when climatic conditions limit early season growth and favor late spring growth, applying all N at topdress (no preplant) tended to provide greater canola grain yield.